New findings of neogene tortoises Titanochelon kayadibiensis sp. nov. and Protestudo bessarabica (Riabinin, 1918) (Testudinidae) from the Miocene of western Turkey, with a review of fossil turtles of Turkey - Volker Karl, Hans; Staesche, Ulrich; Safi, Amtyaz (SPC Journal of Environmental Sciences, 2020)
Fossil remains of turtles were discovered in various localities of Lower to Upper Miocene within the western part of Turkey. We revised the taxonomic position and describe the systematic paleontology, distribution, phylogeny and palaeo-environments of two Neogene taxa Titanochelon kayadibiensis sp. nov. and Protestudo bessarabica (Testudinidae) of Western Turkey and give an updated list of fossil turtles of Turkey which include Trionyx triunguis (Forskål, 1775), Mauremys aristotelica Vlachos et al, 2019, Testudo marmorum Gaudry, 1862, Protestudo bessarabica Riabinin, 1918 and Titanochelon kayadibiensis sp.nov.Â Â